1972
DOI: 10.1524/zkri.1972.136.3-4.273
|View full text |Cite
|
Sign up to set email alerts
|

Refinement of the structure of anatase at several temperatures*

Abstract: The crystal structure of anatase was refined at several temperatures between 25°C and 800°C using single-crystal x-ray diffraction data. The only structural parameter, the z coordinate of oxygen, changes regularly from 0.2081(2) at 25°C to 0.2076(3) at 800°C. This change is about an order of magnitude smaller than that proposed by HORN and SCHWERDTFEGER (1971) to explain the temperature dependence of electron paramagnetic resonance spectra of anatase. The thermal vibrations of the titanium ions are isotropic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
167
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 379 publications
(186 citation statements)
references
References 11 publications
19
167
0
Order By: Relevance
“…The structures are rearranged from Ref. [44,45] The CW-EPR analysis of trapped electron centers (Ti 3+ ) in -rutile and brookite performed in the present work allowed us to accomplish a picture of the EPR features of such centres for all the polymorphs of titanium dioxide, whose crystal structures are reported in Scheme 1A. This analysis started with the EPR investigation of anatase [23], followed by the study on the properties of the interstitial Ti 3+ in rutile.…”
Section: Electron Trapping In Brookitementioning
confidence: 96%
“…The structures are rearranged from Ref. [44,45] The CW-EPR analysis of trapped electron centers (Ti 3+ ) in -rutile and brookite performed in the present work allowed us to accomplish a picture of the EPR features of such centres for all the polymorphs of titanium dioxide, whose crystal structures are reported in Scheme 1A. This analysis started with the EPR investigation of anatase [23], followed by the study on the properties of the interstitial Ti 3+ in rutile.…”
Section: Electron Trapping In Brookitementioning
confidence: 96%
“…The c-axis length for bulk anatase is 9.515Å (Space group I41/amd). [19] On comparing the average value of 'c' for the a-TiO2/NGO films with thickness from 20nm to 100nm, it can be observed that its value changes from 9.367Å to 9.487Å for 20nm to 60nm films. However the value of 'c' decreases at 80nm to 9.484Å and is decreased further for 100nm to 9.469Å, as compared to the 60nm thick films.…”
Section: Submitted Tomentioning
confidence: 99%
“…The crystal structure of the NGO substrate is orthorhombic with lattice parameters [21] [19] The lattice mismatch between the NGO substrate and anatase is slightly different along the a and b directions, with values of 2.14% and 1.91% respectively. These values are slightly greater than the measured average a and b strains of 1.67 and 1.44% respectively for the thinnest 20nm films (see Figure 1), as would be expected, and confirm that an in-plane biaxial strain originates due to lattice mismatch between the film and the NGO substrate.…”
Section: Submitted Tomentioning
confidence: 99%
“…The presence of anatase was confirmed by μ-XRD in samples 1, 2a and 9. At low temperature, anatase is the most common polymorph of titanium dioxide, stable in 600-900°C range, whereas above this temperature threshold anatase converts into rutile, depending on grain size, atmosphere and nature and amount of impurities [25]. Therefore, the presence of anatase may indicate a firing temperature lower than 900°C.…”
Section: Milpillas Phase (1200-1450 Ad)mentioning
confidence: 99%